Degenerative temporomandibular joint changes associated with recent-onset disc displacement without reduction in adolescents and young adults. Issue 3 (March 2017) - Lei, Jie; Han, Jianhui; Liu, Muqing; Zhang, Yi; Yap, Adrian U-Jin; Fu, Kai-Yuan
Abstract: This study evaluated the occurrence of degenerative temporomandibular joint (TMJ) changes in adolescents and young adults with recent on-set disc displacement without reduction (DDw/oR) using high-resolution cone beam computed tomography (CBCT). The associations between types of osteoarthrosis (OA) changes and clinical factors including disease duration were also examined. CBCT and clinical data of 300 patients (84.70% females, mean age 20.93 ± 4.77 years) diagnosed with unilateral DDw/oR (≤12 months) based on RDC/TMD were acquired. CBCT images of both symptomatic and contralateral asymptomatic TMJs were independently evaluated and scored by two radiologists. Associations between OA changes and gender, age, mouth opening and duration of DDw/oR were analyzed statistically. Condylar OA changes were present in 59.30% of the joints with DDw/oR. Early-stage OA changes (loss of continuity of articular cortex and/or surface destruction) constituted most (45.67%) of the alterations. Prevalence of early-stage OA increased from 24% to about 60% one month after TMJ closed-lock occurred. Logistic regression analysis showed the risk of developing early-stage OA changes was 5.33 times higher one month after onset of DDw/oR. A high prevalence of degenerative TMJ changes was observed with recent on-set DDw/oR in adolescents and young adults. Early diagnosis and intervention of DDw/oR is therefore prudent.